2016
DOI: 10.18295/squmj.2016.16.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intracervical Foley Catheter for Induction of Labour in Cases of Previous Caesarean Section: Experience of a single tertiary centre in Oman

Abstract: abstract:Objectives: This study aimed to evaluate rates of success and perinatal complications of labour induction using an intracervical Foley catheter among women with a previous Caesarean delivery at a tertiary centre in Oman. Methods: This retrospective cohort study included 68 pregnant women with a history of a previous Caesarean section who were admitted for induction via Foley catheter between January 2011 and December 2013 to the Sultan Qaboos University Hospital, Muscat, Oman. Patient data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…They recommend that if needed, mechanical induction should be used instead of medical induction by prostaglandins. 18 Most of the demographic data of the present study is similar to a study by Hazel Gonsalves et al 19 The number of women with history of vaginal delivery, age group of the patients, BMI are similar to our study, but their study involves mostly term patient's contrary to ours which has mostly pre term patients with obstetric complications. Younger age of the patients and previous vaginal delivery were the statistically significant determinants in their study on the success of induction whereas in our study, younger age of the patient, lesser gestational age and history of previous vaginal delivery showed statistical significance as the determinants of successful induction.…”
Section: Discussionsupporting
confidence: 88%
“…They recommend that if needed, mechanical induction should be used instead of medical induction by prostaglandins. 18 Most of the demographic data of the present study is similar to a study by Hazel Gonsalves et al 19 The number of women with history of vaginal delivery, age group of the patients, BMI are similar to our study, but their study involves mostly term patient's contrary to ours which has mostly pre term patients with obstetric complications. Younger age of the patients and previous vaginal delivery were the statistically significant determinants in their study on the success of induction whereas in our study, younger age of the patient, lesser gestational age and history of previous vaginal delivery showed statistical significance as the determinants of successful induction.…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with the induction done with Foley catheter by Sananes et al 26 Studies done by Hemalatha et al, Gonslaves et al, Ben-Aroya et al and also reported no case of uterine rupture. 22,25,27 In the present study, there were no cases of uterine hypertonicity and tachysystole. This is in agreement with the study done by Ziyyaudin et al, Hemalatha et al and Gonsalves et al 10,22,25 In the present study population of 24 subjects, only one case of vaginal bleeding was observed and emergency LSCS was done.…”
Section: Discussionsupporting
confidence: 40%
“…22,25,27 In the present study, there were no cases of uterine hypertonicity and tachysystole. This is in agreement with the study done by Ziyyaudin et al, Hemalatha et al and Gonsalves et al 10,22,25 In the present study population of 24 subjects, only one case of vaginal bleeding was observed and emergency LSCS was done. In the study done by Gonzalves et al, out of 68 study subjects, 4 women experienced vaginal bleeding following the insertion of the Foley catheter; 3 had minimal bleeding and subsequently underwent a successful VBAC, but one had heavy vaginal bleeding and foetal bradycardia, resulting in an emergency CS.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations